Controlling the hydraulic resistance of membrane biofilms by engineering biofilm physical structure. (15th February 2022) - Desmond, Peter; Huisman, Kees Theo; Sanawar, Huma; Farhat, Nadia M.; Traber, Jacqueline; Fridjonsson, Einar O.; Johns, Michael L.; Flemming, Hans-Curt; Picioreanu, Cristian; Vrouwenvelder, Johannes S.
Highlights: Biofilm hydraulic resistance can dominate overall filtration resistance (>50%). Hydraulic resistance of membrane biofilms is largely governed by biofilm density. Biofilm density can be reduced by nutrient manipulation and reduced shear stress. Uncertain if laboratory biofilm models have fidelity to fouling layers in full-scale systems. Abstract: The application of membrane technology for water treatment and reuse is hampered by the development of a microbial biofilm. Biofilm growth in micro-and ultrafiltration (MF/UF) membrane modules, on both the membrane surface and feed spacer, can form a secondary membrane and exert resistance to permeation and crossflow, increasing energy demand and decreasing permeate quantity and quality. In recent years, exhaustive efforts were made to understand the chemical, structural and hydraulic characteristics of membrane biofilms. In this review, we critically assess which specific structural features of membrane biofilms exert resistance to forced water passage in MF/UF membranes systems applied to water and wastewater treatment, and how biofilm physical structure can be engineered by process operation to impose less hydraulic resistance ("below-the-pain threshold"). Counter-intuitively, biofilms with greater thickness do not always cause a higher hydraulic resistance than thinner biofilms. Dense biofilms, however, had consistently higher hydraulic resistances compared to less dense biofilms. The mechanism by which density exerts hydraulic resistance is reported in the literature to be dependant on the biofilms' internal packing structure and EPS chemical composition (e.g., porosity, polymer concentration). Current reports of internal porosity in membrane biofilms are not supported by adequate experimental evidence or by a reliable methodology, limiting a unified understanding of biofilm internal structure. Identifying the dependency of hydraulic resistance on biofilm density invites efforts to control the hydraulic resistance of membrane biofilms by engineering internal biofilm structure. Regulation of biofilm internal structure is possible by alteration of key determinants such as feed water nutrient composition/concentration, hydraulic shear stress and resistance and can engineer biofilm structural development to decrease density and therein hydraulic resistance. Future efforts should seek to determine the extent to which the concept of "biofilm engineering" can be extended to other biofilm parameters such as mechanical stability and the implication for biofilm control/removal in engineered water systems (e.g., pipelines and/or, cooling towers) susceptible to biofouling.